Iceland's Accession to the Antarctic Treaty - Tamm, S; Julia Jabour; Johnstone, RL (2017)
On 13th October 2015, Iceland quietly submitted its instrument of accession to the Antarctic Treaty to the US Department of State (the depositary for the Antarctic Treaty). Iceland’s accession was not accompanied by any official declaration or public discussion in Iceland or elsewhere. This paper investigates some of the factors that are likely to have spurred the decision to join the Antarctic treaty system, examines current Icelandic interests in the Antarctic and proposes constructive policies to enhance Icelandic involvement in Antarctic governance and cooperation following the accession. The authors conclude that logistical operations and adventure tourism involving Icelandic companies in the Antarctic are the most likely triggers for the accession and they propose that Iceland consider ratification of the Protocol on Environmental Protection to the Antarctic Treaty (Madrid Protocol).